The Effect of Brisk Walking Exercise on Changes in Rheumatoid Arthritis Factor in Older Women with Rheumatoid Arthritis Symptoms - Majid, Muhammad Faisal (Sports Medicine Curiosity Journal, 2023)
Rheumatoid arthritis (RA) is an autoimmune disease in which the joints become inflamed causing swelling, pain and often eventually causing damage to the inside of the joint. Hence, physical exercise is believed could gives healing effects on health issues. The research design used by researchers is quasi-experimental designs with a pre-test – post-test group design without a control group. The results showed that there was a significant effect of brisk walking exercise on rheumatoid factor levels (IU/ml) in elderly women with rheumatoid arthritis symptoms with a significant value (Sig) <0.05. It means giving Brisk Walking Exercise to changes in Rheumatoid factor levels (RF) has a significant effect on elderly women with rheumatoid arthritis symptoms.